Dinámica de los Contaminantes Atmosféricos emitidos por Fuentes Fijas en el Cantón Latacunga. - Tisalema Moreno, Diana Maribel (2017)
In the recent years, the atmosphere pollution has become one of the main environmental problems because of natural disasters and the impact of the anthropogenic activities, which have generated an injurious effect in the air quality in the health of the living beings. It has caused concern in society and the authorities. It has regarded important the research in atmospheric pollution caused by the industries that is found in Latacunga city, Tanicuchi parish classified as Fuentes fijas. This research has as objective to provide information about the aspects related to the atmospheric pollution which tends to expand about means that contribute to air pollution, emission and types of contaminants sources. The variables such as: the access to sampling point, coordinates, altitude, texture of the soil, type of surface, flora and fauna were used to make the environmental diagnosis or basis line. The environmental diagnostic was determined that 15 points are the most affected, allowing to know the degree affectation that the contaminating Fuentes fijas generate in the influence area. It performed the identification of the affected sources such as: soil, flora and fauna through linear transects of 10 meters surrounded the point and with 500 meters of distance for each example. According to the methodology used has gotten real and objective information through field visits for the situational diagnosis of the surroundings of “Familia Sancela” enterprise. It was determined that the population has multiple consequences affecting the growing and reproduction of the plants, the modification of the vegetal cover. It is introduced a georeferential map where it was identified different locations of the polluted fuentes fijas in Tanicuchi parish through the use of GPS and an QGIS free software.